The Effectiveness of Linear and Nonlinear Pedagogical Approaches in Team-Invasion Ball Sports: A Systematic Review - Liam Bromilow; Nikki Milne; Carl T. Woods; Caroline K. Dowsett; Justin W. L. Keogh (Sports Medicine - Open)
Abstract Background In the sport sciences, skill development is often (implicitly) explained through two metatheoretical perspectives: interactionism and transactionism. Given certain assumptions, the former adheres to a linear pedagogical approach to learning, while the latter follows a nonlinear pedagogical approach. The aim of this systematic review was to compare the effects of linear and nonlinear pedagogical approaches on the development of technical and tactical skills in team-invasion ball sports. Methods A systematic search of six databases (EmBase, PubMed, SPORTDiscus, OVID Medline, CINAHL, and OVID PsychInfo) was undertaken from root to 1st May 2024. Included studies were critically appraised using the ROBINS-I and RoB2 instruments. A narrative and descriptive synthesis approach was utilised. Results From 7450 potential records, nine studies were included, which explored the effects of a nonlinear versus linear pedagogy for developing technical and tactical skills in team-invasion ball sports. While, for most outcomes, the results showed there were no significant differences, nonlinear pedagogy did appear more favourable in 34% of technical outcomes. Further, descriptive synthesis of four studies revealed that nonlinear pedagogy was significantly better for developing tactical skills in 66% of outcomes. Conclusions While based on limited studies, linear and nonlinear pedagogical approaches appear to achieve similar results with regards to technical skill development. However, nonlinear pedagogy was favoured in some studies. With regards to tactical skill development, nonlinear pedagogical approaches appear better than linear approaches. Further high-quality research is needed to confirm these findings and examine how they may be implicated by the representativeness of the assessment instruments. Key Points Both linear and nonlinear pedagogical approaches assist with skill development in team-invasion ball sports. Nonlinear pedagogical approaches generally result in greater effects when developing tactical skills, while most literature shows there are no significant differences between approaches when developing technical skills. Further high-quality research exploring the effects of these pedagogical approaches is required to substantiate these findings. Questions remain regarding the representativeness of the assessment instruments used in the studies included in this review. Registration This systematic review is registered with Open Science Framework- https://osf.io/za247/